The effect of active learning strategies on students’ attitudes towards English: a study at Universiti Teknologi Petronas - Kamarulzaman, Laily Murny; Abdul Ghani, Mohammad Taufiq; Wan Daud, Wan Ab Aziz (UMK Press, 2018)
The availability and diversity of instructional methods in English classroom has increased tremendously in the last decade. As a result, the lecture format has been redesigned and more interactive teaching and learning strategies have been developed. Hence, this paper explores the effect of active learning on students’ attitudes in learning English as a second language (ESL). Active learning techniques were employed in teaching and learning process for the duration of 12 weeks. At the end of the semester session 2017/2018, a set of questionnaire on students’ attitudes towards English language and active learning was administered to 100 foundation students of English language course at Universiti Teknologi Petronas. The descriptive quantitative analysis was employed to analyse the data by using IBM SPSS statistical software. Findings of the study show that most students have positive attitude towards both English and the use of active learning to teach English. Besides, the higher-order cognitive skill and soft-skill could be developed through the use of active learning strategies.